2012
DOI: 10.1007/s10337-012-2232-6
|View full text |Cite
|
Sign up to set email alerts
|

An MC3T3-E1 Cell Line Biomembrane Extraction and HPLC–ESI-MS n Method for Simultaneous Analysis of Potential Anti-Osteoporosis Components of Epimedium koreanum

Abstract: Aerial parts of Epimedium koreanum Nakai have been used as Herba Epimedii in China. Its anti-osteoporosis effect has attracted much attention in recent years. In this study, a method involving osteoblastic cell (MC3T3-E1 cell line) extraction and high-performance liquid chromatography-electrospray ionisation-mass spectrometry (HPLC-ESI-MS n ) was developed for screening of potential anti-osteoporosis agents in E. koreanum. Four compounds identified as epimedin A, epimedin B, epimedin C and icariin were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Total flavones of Epimedium (TFE) inhibited reduction of procollagen type I N-terminal propeptide (PINP), and increased serum osteocalcin and type I collagen in OVX rats (13,14). Icariin, one of the major components of Herba Epimedium, decreased activities of serum tartrate-resistant acid phosphatase (TRAP) and bioactive components could stimulate the proliferation, differentiation and mineralization of osteoblasts (12,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), suppress the adipogenesis of bone marrow-derived mesenchymal stem cells (BMSCs) (41)(42)(43)(44), inhibit the proliferation and differentiation of osteoclasts (45)(46)(47), and induce apoptosis and cell cycle arrest and suppress bone resorption of osteoclasts (48). In addition, icariin was found to significantly attenuate oxidative stress and apoptosis and preserve viability and osteogenic potential of osteoblasts exposed to hypoxia, which indicated that its anti-osteoporotic effect might be attributed to its anti-hypoxic activity (49).…”
Section: In Vivo Findingsmentioning
confidence: 99%
“…Total flavones of Epimedium (TFE) inhibited reduction of procollagen type I N-terminal propeptide (PINP), and increased serum osteocalcin and type I collagen in OVX rats (13,14). Icariin, one of the major components of Herba Epimedium, decreased activities of serum tartrate-resistant acid phosphatase (TRAP) and bioactive components could stimulate the proliferation, differentiation and mineralization of osteoblasts (12,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), suppress the adipogenesis of bone marrow-derived mesenchymal stem cells (BMSCs) (41)(42)(43)(44), inhibit the proliferation and differentiation of osteoclasts (45)(46)(47), and induce apoptosis and cell cycle arrest and suppress bone resorption of osteoclasts (48). In addition, icariin was found to significantly attenuate oxidative stress and apoptosis and preserve viability and osteogenic potential of osteoblasts exposed to hypoxia, which indicated that its anti-osteoporotic effect might be attributed to its anti-hypoxic activity (49).…”
Section: In Vivo Findingsmentioning
confidence: 99%
“…For example, HaCaT, HUVEC, and RAW 264.7 cell lines were chosen as the targets to screen the bioactive compounds from Fuzhengzhiyang decoction, and 14 types of potential active compounds were identified (Chen et al, 2020). Based on the specific binding reaction of osteoblast lines, the active ingredients have been successfully identified from Epimedium koreanum (Wang et al, 2012), Herba Epimedii (Jin et al, 2013), and Er‐Xian decoction (Wang, Xu, Wang, et al, 2019). Although living cells have a satisfactory number of targets, the isolation of living cells from NP extracts and preservation of their biological activity as much as possible are some of the challenges of this method.…”
Section: Applications Of Immobilized Biomembrane Materialsmentioning
confidence: 99%
“…Besides icariin, a number of flavonol constituents of Epimedium are also osteo-active. Thus, epimedins A ( 40 , Figure 1), B ( 38 , Figure 1), C ( 39 , Figure 1) and icariin were demonstrated to interact with MC3T3-E1 cells in a biomembrane extraction model [211], and epimedin B and epimedin C promoted the proliferation of UMR-106 cells [178]. In a zebrafish model of anti-osteoporosis, epimedin A and baohuoside-1 (icarisinde II) ( 41 , Figure 1) were found to be active [212].…”
Section: Natural Products With Osteoprotective and Related Activitiesmentioning
confidence: 99%